Avaliação de componentes da susceptibilidade genética à fenótipos neuropsiquiátricos utilizando metanálise - Luiza Prado Rosa de Matos (2015)
INTRODUCTION: Neuropsychiatric disorders are predominantly multifactorial diseases. The presence of heterogeneity is a complicating factor in understanding the mechanisms involved in the development of these diseases, performing diagnostics and selecting an appropriate treatment. Personalized medicine, in conjunction with the development of biomarkers, aims to solve these problems. Its application assists in establishing effective therapeutic measures, taking into account inherent characteristics of the individual. This study aimed to evaluate the potential of, dopamine receptor gene D1 (DRD1), rs4532 polymorphism to be used as a biomarker for antipsychotics treatment response and the potential of apolipoprotein E E4 allele (ApoE E4) to participate in the risk of neurocognitive disorder manifestation in patients with the human immunodeficiency virus (HIV). METHODS: A systematic review with meta-analysis was performed seeking to evaluate the existence of a genetic association between: DRD1 polymorphism and antipsychotics treatment response and (2) ApoE E4 allele and the manifestation and cognitive disorders in patients with HIV. Epidemiological and clinical data were extracted and a meta-analysis was conducted. RESULTS: Our results indicated no association between DRD1 rs4532 polymorphism and antipsychotic treatment response, nor with clozapine treatment response. An association was observed between ApoE E4 allele with, clinically symptomatic, cognitive impairment in studies that used neuropsychological test battery as a neuropsychological evaluation tool, but no association was observed between ApoE E4 allele with, symptomatic, cognitive impairment or dementia in patients with HIV, individually, in studies with other clinical evaluation methods or when all groups were combined. The results show that the genetic polymorphisms studied are not associated with the evaluated neuropsychiatric phenotypes, therefore, they should not be used as biomarkers.